Performance analysis of a direct injection diesel engine using Biodiesel and additives / Desmond Jayson ... [et al.] - Jayson, Desmond; Mat Taib, Norhidayah; Abu Mansor, Mohd Radzi; Mohamad, Taib Iskandar; Ilham, Zul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Combustion in diesel engines release harmful gases leading to air pollution. Biodiesel, a mixture of petroleum-based and plant-derived hydrocarbon, is known for its potential to reduce harmful emissions in diesel engines. However, one of the main problems with biodiesel is high carbon deposition due to very long carbon chain content. Additives are used as carbon deposition breaker for the engine. This paper presents the effects of such additives on engine performance fuelled with oil palm biodiesel. A single cylinder direct injection diesel engine, YANMAR TF90 were run with different blends of diesel-biodiesel and 2.0ml Decarbonising High Performance (DHP) as additives. Results of the in-cylinder pressure were then analyzed to determine the combustion characteristics. Biodiesel produced lower gas pollutant compared to pure diesel, but due to high viscosity and low heating value, the engine performance was lower than diesel. However, the viscosity reducer and heating value improver additive were found to improve engine performance.